Perancangan Sistem Informasi dan Sarana Pelaporan Kasus Bullying Berbasis Web Menggunakan Teknologi Pemograman PHP dengan Framework Laravel - Sutono; Tri Widayanti; Bety Agustina Rahayu (Jurnal Infokes, 2020)
Bullying is still a troubling social problem. Bullying cases that occur in high school students have caused many problems both physically and psychologically. Bullying is a phenomenon that is very much, rooted, passed down from generation to generation. The seriousness of bullying is a big problem for all of us. The level of knowledge and concern for teachers, parents, health service teams, and the Indonesian people towards bullying is still low. Information systems are needed for management in making decisions to overcome bullying problems. Researchers in this study created a system that can be used as a means of delivering information from students to schools. The creation of this system is based on a system that is easily accessible, secure, and guarantees the confidentiality of the complainants. So that this product can help schools identify cases of bullying in schools, who are the perpetrators of bullying, and victims of bullying, with the hope that schools can stop the chain of bullying events and prevent bullying at schools. The scheme in this study is to design a website that reports bullying and provides information. The system design model used in this study is a prototype model and data was collected through observation, interviews and literature study. The programming language used is PHP and software for designing interfaces using the laravel framework. Making a database using MySQL with the XAMMP application.